Synergistic effects of piezoelectric actuators and electrode architecture in alkaline water electrolysis - da Silva, João Pedro Parreira e Reis; de Souza, Reinaldo Rodrigues; Pereira, José Socha; de Oliveira, Jeferson Diehl [UNESP]; Moita, Ana Sofia (Elsevier, 2025)
The transition to sustainable energy systems has highlighted the need for efficient green hydrogen production. Alkaline water electrolysis (AWE) is a proven method, but its performance is hindered by gas bubble accumulation and poor mass transport at the electrode–electrolyte interface. This study addresses these challenges by combining acoustic excitation and surface-modified nickel foam electrodes to enhance hydrogen evolution in a lab-scale AWE system. A 30 % (w/w) KOH electrolyte was used, with piezoelectric transducers coupled externally to a metallic rod connected to the electrodes, allowing ultrasonic actuation at 20, 40, 60 kHz and 11.059 MHz—an approach differing from conventional ultrasonic baths or probes. Nickel foam electrodes with 110 PPI porosity were tested in three configurations: (i) 1 mm thick, uncoated; (ii) 1 mm with diatomite–epoxy coatings via dip-coating; and (iii) 1 mm with carbon nanotubes (CNTs) deposited using a flame synthesis method; as well as (iv) uncoated 2 mm thick foam. Analytical techniques included polarization and efficiency curves, SEM, and wettability analysis. The 2 mm foam showed the best overall performance without ultrasonic assistance. Without ultrasound, CNT-coated electrodes delivered the highest efficiency, but ultrasound exposure led to partial detachment and performance loss. Diatomite–epoxy coatings initially blocked porosity, reducing efficiency, but ultrasonic degradation of the coating improved electrolyte access and gas release. Uncoated nickel electrodes exhibited modest, consistent benefits from 60 kHz ultrasound, with a 4 mV overpotential drop and up to 0.9 % efficiency gain. These results suggest that integrating acoustic actuation with electrode surface engineering holds promise for advancing AWE performance.